Responsabilidade social na Ciência da Informação: uma análise a partir da Brapci - Souza, Vanessa Maria (Universidade Federal de São Carlos, 2024)
Understanding Information Science as an essentially social field, the understanding of the concept of social responsibility that prevails in Brazilian literature is highlighted. Through exploratory and descriptive research with a qualitative and quantitative approach, we seek to understand how the concept of social responsibility is used in Information Science. To this end, the following specific objectives were met: a) contextualize Information Science as an Applied Social Science, in order to understand its social role; b) map scientific articles and complete works published in events that adopt the term social responsibility in the period from 2000 to 2023, by searching the Information Science Database; c) check the authors who publish the most on the topic and the temporal evolution of these studies; and d) the main keywords adopted and the configuration of these searches. In order to categorize the conceptual similarities and differences of the uses and applications of the concept, content analysis was used, adopting Freire's (2014) analysis categories, comprising: a) epistemology (social responsibility as the foundation of Information Science); b) theory (policy and management actions in the information society); and c) application (in units and for information professionals). The results reveal greater involvement of Brazilian researchers with issues related to social responsibility as the foundation of Information Science. The conclusion points to a growing interest in the scientific community in the topic, with multiple investigative scopes being considered that discuss social responsibility from the perspective of ethics, culture, sexual diversity, psychoanalysis, social inclusion and public policies.
Social responsibility in Information Science: an analysis from Brapci
Keywords: Ciência da Informação; Responsabilidade social; Produção científica; Brapci; Information Science; Social responsability; Scientific production; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO